Pengaruh Disiplin dan Motivasi Kerja terhadap Produktivitas Pegawai Disdukcapil Tabanan - Ayu Rainingsih, Ni Ketut; Wijaya, Putu Yudy; Surya Diputra, Gde Indra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The formulation of the problem and the objectives of this study were to determine the effect of Discipline and Work Motivation on the Productivity of Tabanan Disdukcapil Employees. The population of this study were all employees of the Tabanan Population and Civil Registry Office, totaling 60 people. The sample used in this study was 60 respondents who were determined by the probability sampling technique. The data in this study were collected through observation, interviews, questionnaires and then tested using multiple linear regression analysis techniques. Based on the results of the study it can be seen that work discipline has a positive effect on employee work productivity. Work motivation has a positive effect on employee work productivity. Work discipline and work motivation have a positive effect on employee work productivity. The magnitude of the influence of independent variables on employee work productivity is 80.2%. Seeing the results of the research, employees at the Tabanan Population and Civil Registry Service in the future must be given job training so that later their abilities will increase so that they can complete assignments on time.